D/H exchange in C–H bonds of fatty acids: Implication for geographical discrimination of food materials - Yamanaka, Atsuko; Goto, Akiko S.; Korenaga, Takashi (Food Chemistry, 2013)
► Fatty acid phospholipid bilayers are exposed to 0–50% D2O in this study. ► D/H on fatty acids is clearly exchanged (e.g., 93–328‰ in 50% D2O) for 12h. ► However, this exchange is considered to be insubstantial in natural environments. ► These results imply that the hydrogen isotope ratio can be useful in tracing of food materials. The stable isotope analysis of non-exchangeable hydrogen in food materials has been believed as a powerful tool for tracing geographical origins and delivery of the materials. However, little information is available for the D/H exchanges even in hydrophobic molecules, which leads to potential uncertainty on the observed results. To further evaluate the reliability of hydrogen isotopes of organic molecules, we examined the isotope exchangeability in fatty acids within phospholipid bilayers exposed to D2O for 12h. The results indicate that the isotope ratio is clearly increased during all examines (e.g., 93–328‰ in 50% D2O), in which its magnitude depends on type of fatty acids and state of bilayers. However, these results also indicate very clearly that the observed exchange rate is negligible if samples are exposed to natural abundance of deuterium (0.0156%) in natural and laboratory environments before/during analysis.